Machine Learning for Multiobjective Evolutionary Optimization in Python for EM Problems - Boryssenko, Anatoliy; Herscovici, Naftali (Digest - IEEE Antennas and Propagation Society. International Symposium (1995), 2018)
A highly efficient algorithm for the optimization of EM problems is proposed. The algorithm is mostly based on Python open-source libraries and was successfully used in the development of antennas and arrays using HFSS.